Analysis of Factors Influencing the Motivation of Hungarian Junior Handball Players - Peter Karacsony; Kornel Krupanszki (OVS LLC, 2023)
Study purpose. In sports, just like in everyday life, motivation plays an important role in achieving individual goals. Motivation is an individual's decision to engage in certain activities and make various efforts to do so. Sports require a continuous, constant effort from individuals, so it is even more important here that the athlete has the necessary motivation. Without motivation, it is not possible to do sports at a high level in the long term. The aim of the study was to examine the sports motivation factors of handball players in the Hungarian junior classes. Handball is one of the most popular sports in Hungary. As a result, it can be said that, from the point of view of the long-term success of the sport, it is essential to know the factors that motivate youth athletes. Materials and methods. We collected the data required for the research using a questionnaire. The research took place in the fall of 2022, with 190 youth athletes interviewed. During our research, we established that internal and external motivational factors are equally important for Hungarian youth handball players. Results. With statistical calculations, we show a significant relationship between the athletes' motivation and the joy caused by sports, the avoidance of disappointment caused to the environment due to the cessation of sports, and the sports results achieved. Conclusions. The results of the study will be a useful resource for those interested in the sport of handball, to better consider the motivational factors that help to understand the motivation of young athletes and which are important in order to consistently provide a high level of performance.